Hello :
the common ratio is r = -95-(-100)=5
the general terme is : un= u1+(n-1)r
un = -100 +(n-1)(5)
un =-100 +5n-5
un = 5n-105
The last term is : 100
un =100
5n-105 = 100
5n =205
n = 41 (Number of terms)
The last term is : u 41
<span>the sum is : S= (41/2)(-100+100)=0</span>
<span>A) 5x + 7y = 3
B) 2x + 3y = 1
Multiplying Equation B by -2.5
</span><span>B) -5x -7.5y = -2.5 Then adding this to Equation A)
A) 5x + 7y = 3</span>
-.5y = .5
y = -1
Since
<span>2x + 3y = 1 then
2x -3 = 1
then x = 2
</span>
Answer:
25
Step-by-step explanation:
Expression: <em>(2⁸ ⋅ 5⁻⁵ ⋅ 19⁰)⁻² ⋅ (5⁻²/2³)⁴ ⋅ 2²⁸</em>
Inner-most powers: 2⁻¹⁶ • 5¹⁰ • 1 • 5⁻⁸/2¹² • 2²⁸
Combine like terms: 2¹² • 5²/2¹²
Cancel out: 5²
Solve: 25
Altitude is another word for height so it would be the first answer
Antideritiive
antideritive of is
antiderititve of a constant is that constant times x
so
antideritive of is
andtideritivee of 4 is 4x
total is
D is answer